(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The security concern in RPL-based IoT networks has gained a close attention by the researchers in the recent past years. This is due to the inherent constraints of nodes and the frequent change in the network topology. This makes the network vulnerable to various attacks that intend to disrupt the network availability and nodes resources. Heavy and decentralized algorithms seeking to enable the security in RPL networks as cryptographic schemes or expensive solutions are not convenient due to intrinsic characteristics of IoT nodes. In this paper, we propose and analyse a new internal hybrid routing attack against RPL, named SSDH for Selective Sub-DODAGs Hiding attack. The intruder node performing the present attack intends to isolate and exhaust the resources of a targeted subset of nodes by a selective hiding, based on its routing table. Compared to other known isolation attacks, the proposed one shows a silent malicious behavior, in which the root never knows about the isolated nodes. After the selective hiding process by dropping all packets coming from its direct or indirect children nodes, the intruder node follows its malicious behavior by provoking the victim nodes to conduct a DIO flooding based on falsified DIO messages. Simulation results obviously depict the harmful disruption of the present attack in different scenarios of RPL-based networks, by measuring the main QoS metrics: Control overhead, energy consumed, packet delivery ration and average delay. It should be noticed that the present paper describes the process of the new proposed at- tack and its effect, where the preventive and mitigation solutions will be the subject of a future work